Impact of stocking density and dietary nano-zinc supplementation on stress indicators, immunity, and DNA damage in broiler chickens - Sevim, Ö; Boyacıoğlu, M; Yılmaz, ÖB; Aydın, AK; Özdemir, ÖS; Reman Temiz, A; Khamseh, EK; Ahsan, U; Kuter, E; Tatli, O; Yıldırım, EK (Journal of the Hellenic Veterinary Medical Society, 2023)
Effects of stocking density (SD) and nano zinc on oxidative status, immune function, and DNA damage in broilers were examined in the current study. Totally 480 one-day-old male broilers (Ross 308) were randomly divided into 4 treatments each contained 8 replicates. A 2 ´ 2 factorial arrangement with two groups for dietary zinc (Zn) form (inorganic or nano) and two groups for SD (low = 12 birds/m2 and high = 18 birds/m2) was conducted. Basal diets based on the corn-soybean meal were formulated. Relative liver weight was lower (P<0.05) in broiler subjected high stocking density (HSD) but other lymphoid organ weights did not affect. Relative lymphoid organ weights were not affected by dietary nano zinc. HSD increased the serum corticosterone level of broiler (P<0.05) but did not affect the blood heterophil:lymphocyte ratio, serum glutathione, superoxide dismutase, and malondialdehyde levels. Dietary nano zinc had no effect on these stress indicators. Serum interferon-gamma, interleukin 12, and interleukin 18 levels were not affected by HSD. Dietary nano zinc tended to reduce the interferon-gamma level (P=0.05) but did not affect interleukin 12, and interleukin 18 levels in broiler. Eeither HSD or nano zinc had no effect on DNA damage in lymphocyte. In conclusion, HSD may decrease the relative lymphoid organ weights and increase the stress indicators but did not affect the immunity and DNA damage. Generally, dietary nano zinc had no effect on stress indicators, immunity, and DNA damage in broiler.